Tingkat Empati Mahasiswa Program Studi Bimbingan dan Konseling Universitas Kanjuruhan Malang - Laily Tiarani Soejanto (Indonesian Institute for Counseling, Education and Therapy (IICET), 2016)
Empathy and the ability to see things from the client’s perspective is also important, as is the counsellor’s ability to demonstrate an investment of their time and full attention. The purpose of this study is 1) to know the level of empathy of students Guidance and Counseling Program University of Kanjuruhan Malang; 2) To describe the difference of empathy level of students based on force and gender. The subjects of this study are students Guidance and Counseling Program University of Kanjuruhan Malang class of 2013, 2014 and 2015. The research instrument used is empathy scale which is then processed by using descriptive statistic, Test-t and Anova. The result of this research is 57,5% of students are at high empathy level, 35,7% student are in moderate empathy level, and 6,8% student student is a low; 2) There is no significant difference of empathy level of students based on force 2) There is a significant difference of empathy level based on gender.